Impact of pesticides on farmers: A case study in the highlands - Basri, Syahrul; Saleh, Muh.; Amansyah, Munawir (Universitas Islam Negeri Alauddin Makassar, 2024)
This study investigates the symptoms of pesticide poisoning among vegetable farmers in the highland agricultural area of Pattapang Village, Tinggimoncong Subdistrict, Gowa Regency, South Sulawesi. Utilizing a descriptive method, 296 farmers were surveyed to assess pesticide application practices, personal hygiene, and the use of personal protective equipment (PPE). Data collection was conducted via structured questionnaires, focusing on exposure-related symptoms and contributing factors. Results reveal that 24.7% of respondents reported symptoms such as dizziness, nausea, and headaches, with PPE usage varying significantly—79.4% reported using PPE during pesticide application. However, 54.7% of farmers did not wear gloves, and only 24% used masks. Personal hygiene practices were generally good, with 72.6% of respondents following appropriate measures. The findings highlight the need for improved education and interventions to mitigate health risks associated with pesticide exposure. This study underscores the importance of safe pesticide practices and adequate PPE to safeguard farmer health.